Denitrification by large NAT particles: the impact of reduced settling velocities and hints on particle characteristic - Woiwode, W.; Grooss, Jens-Uwe; Piesch, C.; Orphal, J.; Oelhaf, H.; Molleker, S.; Borrmann, S.; Ebersoldt, A.; Frey, W.; Gulde, T.; Khaykin, S.; Maucher, G. (EGU, 2014)
Vertical redistribution of HNO3 through condensation, sedimentation and evaporation of large HNO3-containing particles inside polar stratospheric clouds (PSCs) plays an important role in the chemistry of the Arctic winter stratosphere. In situ observations by the particle probe FSSP-100 during the RECONCILE campaign indicate unexpected large potential NAT (nitric acid trihydrate) particles inside PSCs. The observations can hardly be explained assuming particles with compact morphology and spherical shape due to limited growing time at temperatures below the existence temperature of NAT (TNAT). Utilizing simulations by the CLaMS and measurements by the airborne Fourier transform infrared spectrometer MIPAS-STR we study the impact of reduced settling velocities of NAT particles on vertical HNO3 redistribution. Reduced settling velocities are expected for spherical NAT particles with low mass density or aspheric NAT particles that might explain the maximum sizes of the particles observed in situ. The results of our study support the hypothesis that denitrification is produced by significantly aspheric (i.e. columnar) compact NAT particles which are characterised by reduced settling velocities.